2007
DOI: 10.1017/s0950268807000027
|View full text |Cite
|
Sign up to set email alerts
|

A long-term observational study of the impact of badger removal on herd restrictions due to bovine TB in the Irish midlands during 1989–2004

Abstract: SUMMARYAn observational study was carried out, using data collected from four areas in the Irish midlands, between 1989 and 2004, to critically evaluate the long-term effects of proactive badger culling and to provide insights into reactive badger culling tuberculosis (TB) prevalence in cattle. Confirmed cattle herd TB incidence is the outcome measure used throughout. Relative to reactive culling, proactive badger culling was associated with a decrease in incidence in each of the 16 years of observation, which… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
26
2

Year Published

2008
2008
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(29 citation statements)
references
References 18 publications
1
26
2
Order By: Relevance
“…Tuyttens et al 2000a, b;Donnelly et al 2006;Woodroffe et al 2006aWoodroffe et al , b, 2007Carter et al 2007). In Ireland, while such perturbations have been reported (O'Corry-Crowe et al 1996), neither reactive or proactive badger removal has yet been associated with increased incidence of tuberculosis in either cattle (Griffin et al 2005a;Kelly et al 2007) or badgers (Corner et al 2008).…”
Section: Introductionmentioning
confidence: 97%
“…Tuyttens et al 2000a, b;Donnelly et al 2006;Woodroffe et al 2006aWoodroffe et al , b, 2007Carter et al 2007). In Ireland, while such perturbations have been reported (O'Corry-Crowe et al 1996), neither reactive or proactive badger removal has yet been associated with increased incidence of tuberculosis in either cattle (Griffin et al 2005a;Kelly et al 2007) or badgers (Corner et al 2008).…”
Section: Introductionmentioning
confidence: 97%
“…The problem has undergone substantial research and review efforts (Gormley and Costello 2003;O'Keeffe 2006;Kelly et al 2007;Corner et al 2008) and Britain (Godfray et al 2004;Reynolds 2006;Bourne et al 2007;King 2007;McDonald et al 2008). Badgers are protected by law in Ireland, both North and South (Whilde 1993), and are ecologically significant animals for example, as ecosystem engineers (Jones et al 1994).…”
Section: Introductionmentioning
confidence: 99%
“…The results from the East Offaly Project (O'Maírtiń et al, 1998) (Kelly et al, 2008) and subsequently the Four Area Project (Griffin et al, 2005) demonstrated the constraining role that wildlife infection was having on bovine TB eradication. While infection arises in other species in Ireland, most noticeably in wild deer, the badger is considered to be the primary wildlife source acting as a maintenance host for the disease.…”
Section: Wildlife Disease Control Strategy Vaccination Development Prmentioning
confidence: 99%